2006
DOI: 10.1080/01674820600646198
|View full text |Cite
|
Sign up to set email alerts
|

The impact of miscarriage on women's pregnancy-specific anxiety and feelings of prenatal maternal–fetal attachment during the course of a subsequent pregnancy: An exploratory follow-up study

Abstract: This study assesses the implications a miscarriage history has on women's pregnancy-specific anxiety and feelings of prenatal maternal-fetal attachment during the 1st and 3rd trimesters of a subsequent pregnancy. Thirty-five pregnant women (N = 10 with a history of miscarriage) volunteered participation completing the Pregnancy Outcome Questionnaire (POQ), the Maternal Antenatal Attachment Scale (MAAS and a demographic/reproductive history questionnaire during the first trimester of pregnancy. Of these, 24 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
56
1
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 52 publications
12
56
1
8
Order By: Relevance
“…However, in our study, we found that women in the second trimester both case and control groups had a higher average PAI score when compared to second, third, trimester. In contrast to our study, Tsartsara and Johnson (2006) found that maternalinfant attachment increased significantly in the third trimester. There was no statistically significant difference between the gestational week and prenatal attachment of the women in the case and control group (p <0.05).…”
Section: Discussioncontrasting
confidence: 55%
“…However, in our study, we found that women in the second trimester both case and control groups had a higher average PAI score when compared to second, third, trimester. In contrast to our study, Tsartsara and Johnson (2006) found that maternalinfant attachment increased significantly in the third trimester. There was no statistically significant difference between the gestational week and prenatal attachment of the women in the case and control group (p <0.05).…”
Section: Discussioncontrasting
confidence: 55%
“…Current medical complications related to the pregnancy exacerbated women's mood and feelings of helplessness, which is an established contributor to pregnancy-specific distress (Tsartsara and Johnson, 2006;Cote-Arsenault and Donato, 2011).…”
Section: Recognising Things Are Not Rightmentioning
confidence: 99%
“…Os aspectos psíquicos do aborto espontâneo de repetição (AER) podem ser potencializados nas gestações subsequentes, podendo determinar elevada frequência de problemas emocionais, como síndromes depressivas e transtornos da ansiedade [2][3][4][5] . Esses sintomas podem, inclusive, perdurar por longos períodos 4 .…”
Section: Introductionunclassified